Risks and sustainability of outdoor ski resorts in China under climate changes - Yanqiang Wei; Jing Li; Dongliang Luo; Xuejie Tang; Zihao Wu; Xufeng Wang (npj Climate and Atmospheric Science)
Abstract Global warming is jeopardizing the artificial snow making conditions, shortening outdoor ski resorts opening days and increasing operation cost, severely threatening the sustainability of outdoor ski industry. The sustainability of 772 outdoor ski resorts in China under RCP 4.5 climate scenarios in 2030 s and 2050 s had been analyzed. (1) The skiing sports developed prominently during 1996 to 2023 and will boom in China in the coming decades. (2) Accelerated global warming is the main threat to the sustainability of outdoor ski resorts of China. However, snowfall isn’t a critical influencing factor in the coming decades. (3) The outdoor ski resorts in south China are facing the most threats and are the most unsustainable resorts. We proposed a nexus of Government-Operator-Skier adaptation framework for adapting climate change threats and advocating the temporal small-scale ski resorts are more adaptive as their high water and energy efficiencies for saving water and electricity resources.